2019
DOI: 10.2460/ajvr.80.6.547
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structure and function characterized across age groups and between sexes in healthy wild-born captive chimpanzees (Pan troglodytes) living in sanctuaries

Abstract: OBJECTIVETo comprehensively characterize cardiac structure and function, from infancy to adulthood, in male and female wild-born captive chimpanzees (Pan troglodytes) living in sanctuaries. ANIMALS 290 wild-born captive chimpanzees. PROCEDURESPhysical and echocardiographic examinations were performed on anesthetized chimpanzees in 3 sanctuaries in Africa between October 2013 and May 2017. Results were evaluated across age groups and between sexes, and potential differences were assessed with multiple 1-way ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…All health assessments were conducted at the housing facilities and by experienced veterinarians as previously described. 22,23 Briefly, once a chimpanzee was anesthetized and unresponsive to external stimuli, the animal was weighed, then transported to an assessment area, where a full health assessment was completed. Each health assessment included a thorough physical examination, blood sampling, morphometric measurements, and cardiac assessment with 12-lead ECG and transthoracic echocardiography.…”
Section: Health and Cardiac Assessmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…All health assessments were conducted at the housing facilities and by experienced veterinarians as previously described. 22,23 Briefly, once a chimpanzee was anesthetized and unresponsive to external stimuli, the animal was weighed, then transported to an assessment area, where a full health assessment was completed. Each health assessment included a thorough physical examination, blood sampling, morphometric measurements, and cardiac assessment with 12-lead ECG and transthoracic echocardiography.…”
Section: Health and Cardiac Assessmentsmentioning
confidence: 99%
“…Echocardiography-After undergoing ECG, chimpanzees were positioned in left lateral recumbency for comprehensive transthoracic echocardiography, which was completed with a commercially available ultrasound machine d and probes e,f as previously described 23 and in line with human guidelines. 25,[45][46][47] To minimize measurement variability inherent with composite echocardiographic measures and to not make any assumptions regarding cardiac geometry in chimpanzees, we chose to use measures of areas and dimensions, instead of measures of volume or mass.…”
Section: Health and Cardiac Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the highly trabeculated LV apex and absence of apical rotation that was observed in almost all animals in our original study (2) was confirmed in this larger cohort. Basic echocardiographic parameters from this cohort have been published (4), and data on trabeculations and rotational mechanics will follow in due course. Confirmation of marked apical trabeculation in chimpanzees across the full age spectrum, including those anesthetized with and without medetomidine, strongly supports the hypothesis that this phenotype represents a defining structural characteristic of the derived chimpanzee heart.…”
mentioning
confidence: 99%